Initial Experiences with the Trenza Embolization Device for the Treatment of Wide-Neck Intracranial Aneurysms: A 12-Patient Case Series - Raj, Rahul; Numminen, Jussi (American Journal of Neuroradiology, 2024)
SUMMARY: The Trenza embolization device is a frame coil implant with flow-disruption properties and is a new alternative to treat challenging mid-to-large-sized broad-neck bifurcation or sidewall aneurysms. We conducted an observational single-center retrospective study of 12 consecutive patients treated for 10 unruptured and 2 ruptured 6- to 12-mm broad-neck bifurcation or sidewall aneurysms with the Trenza device during 2022–2023. The median patient age was 64 years (interquartile range, 59–70 years), 58% were women, the median largest aneurysm diameter was 9.6 mm (interquartile range, 7.5–11.9 mm), the median dome-to-neck ratio was 1.8 (interquartile range, 1.6–1.9), the most common aneurysm locations were the anterior communicating artery (33%) and basilar artery tip (33%). After a median follow-up of 6.5 months, adequate aneurysm occlusion was achieved in 83%. There were 3 major ischemic complications (25%), leading to 2 permanent neurologic deficits (17%) and 1 transient neurologic deficit (8%). There was 1 fatal rupture of a treated aneurysm 1.6 months after the index treatment. Two patients were retreated (17%). Ischemic complications occurred in patients after a too-dense coil packing at the base of the aneurysm. No technical issues related to the device were encountered. In summary, an adequate aneurysm occlusion rate was achieved using the Trenza-assisted coiling technique for otherwise challenging mid-to-large-sized broad-neck aneurysms. Ischemic complications seemed to occur following overdense coiling at the base of the aneurysm.ASAacetylsalicylic acidDAPTdouble antiplatelet treatmentIQRinterquartile range